A study of Islamic customer satisfaction. (1st January 2013) - Noroozi, Ahmad
Customer satisfaction's key role in marketing has led to the development of models to measure this concept. Customer satisfaction has been used as a critical index of business' success. It could gradually find its way through other managerial tools and performance measurements, and has even led to the development of national customer satisfaction indices. In any concept related to the human sciences, kinds of ontological, epistemological, and human nature assumptions do have an effect on the quality of concept. The dominance of utilitarianism over global business environment has driven the concept of customer satisfaction toward a tool to generate more profit. Islamic thought opposes the aforementioned perspective in customer satisfaction. The Muslim way of thought is led by an endeavour to reach God's satisfaction as a final goal of life whether on an individual level or a social level, whether in a for-profit environment or a not for-profit environment. By considering God's satisfaction as the final goal, gaining customer satisfaction would be acceptable. In addition, customer satisfaction has to respect the human position, which in Islamic literature is called Takrim. Using grounded theory to build a theory on this proposition, several interviews with Islamic experts have been conducted.